Breast Implant-Associated Anaplastic Large Cell Lymphoma: A Case Report - Kumkum Vadehra; Jennifer Cai; Rashmi Rekha Bhuyan; Ping Ji; Rose Venegas; Xin Qing (Journal of Hematology and Oncology Research, 2021)
Breast implant-associated anaplastic large cell lymphoma (ALCL) is a recently recognized type of T-cell lymphoma that can develop following breast implants, with morphologic and immunophenotypic features indistinguishable from those of ALK-negative ALCL. Here we report a case of a 58-year-old woman with a history of subglandular silicone implants placed for bilateral breast augmentation 25 years ago, who presented with bilateral breast pain and was found to have bilateral Baker Grade III capsular contracture, and heterogenous fluid collection centered near the left third costochondral articulation, a suspicious left chest wall lesion, and left axillary lymphadenopathy on imaging. A left axillary lymph node core biopsy and an aspiration of the fluid were performed, and no malignant cells were identified. The patient underwent bilateral removal of breast implants and total capsulectomies. Microscopic examination of the capsule surrounding the left breast implant revealed large pleomorphic tumor cells in a fibrinous exudate. By immunohistochemistry, the tumor cells were found to be positive for CD3 (subset), CD4, CD7, CD30 (strong and uniform), and CD43, and negative for CD2, CD5, CD8, and ALK1, supporting the diagnosis of breast implant-associated ALCL. No lymphoma cells were identified in the right breast capsule, confirmed by CD30 stain. Breast implant-associated ALCL is a very rare disease that can develop many years after breast implant placement. Proper evaluation with breast imaging and pathologic workup is essential to confirm the diagnosis in suspected cases. Our case highlights that adequate sampling is important in the investigation of patients with suspected breast implant-associated ALCL.
Keywords: anaplastic large cell lymphoma